Viabilidade de Clostridium difficile em mortadela adicionada de óleos essenciais e teor reduzido de nitrito de sódio - Dias, Nayane Aparecida Araujo (2015)
Clostridium difficile is a mesophilic bacteria, Gram-positive, anaerobic strict, spore former, associated with diarrhea for nosocomial infection, however is every day more related to the ingestion of contaminated food. Because of the growing consumer interest in natural foods with no added chemical preservatives, the essential oils are an alternative, reducing the use of artificial additives such as nitrite. In this study the objective was to determine the minimum bactericidal concentration of different essential oils and their combinations on C. difficile; identify and quantify chemical components of essential oils of Origanum vulgare, Thymus vulgaris and Litsea cubeba, and prepare bologna with reduction of sodium nitrite and adding essential oils, analyzing the growth and sporulation of C. difficile, evaluation by scanning electron microscopy morphological aspects, as well as the effect on color, lipid oxidation, residual nitrite, texture and sensory effects of the product. The Minimum Bactericidal Concentration of the essential oil (EO) O. basilicum was the 1.2%, while O. vulgare and T. vulgaris showed bactericidal effect to 0.3% and L. cubeba to 0.15 %. All essential oils combinations O. vulgare, T. vulgaris and L. cubeba efficient in vitro. Being selected for the bologna preparation, the combination of EO of O. vulgare (0.2%), T. vulgaris (0.05%) and L. cubeba (0.025%) for F1, and F2 for the EO of O. vulgare (0.1%), T. vulgaris (0.1%) and L. cubeba (0.05%). There was no significant difference in theviable cells growth among treatments containing EO and control, however there was an increase approximately 2,5 log10 de NMP/g of viable cells after the fifth day. It was observed an increase of sporulation during storage, especially in F1 with 2.3 log10 NMP/g of endospores in bologna at the end of its storage, reducing pH during storage and greater amount of residual nitrite in F1 with 10.23 ppm and reducing residual nitrite during storage, presenting 18.75 ppm in the first day of storage and 5.11 in the last day. It was observed a higher lipid oxidation (P<0.05) in bologna-control, not being observed significant differences (P>0.05) of oxidation in bologna added EO during all storage time. The EO did not influence the color (P>0.05) of bologna, as the texture reduced the hardness and chewiness during the storage time with increased adhesiveness (P< 0.05). By applying the multiple comparison test, the color was not deferred the control- sample, and the most affected attribute by EO was the flavor, which resulted in lower product acceptance.